PERANAN SEKTOR INDUSTRI TERHADAP PENYERAPAN TENAGA KERJA DI KOTA SURABAYA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2017)
The city of Surabaya is the second largest city in Indonesia after the capital city of Jakarta, as a big city of Surabaya certainly has a variety of supporting sectors that become the leading sectors, one of which is the industrial sector. Various industrial areas can be found easily in this city. As in the middle of the city is in the area Rungkut Rungkut Industri, and so forth. However, even though Surabaya is said to be a big city, Surabaya still has many problems. One of them is the number of unemployed especially in the BPS data in 2013 the number of Surabaya city unemployment increased to 77,861 people from the previous year ie in 2012 which only amounted to 71.861 people only. It is assumed that the number of industries has a positive and significant effect on the absorption of manpower in Surabaya city. In sampling technique to find the data of the researcher using time series technique, while the data taken is data for five consecutive years starting from 2009-2013, used is the latest data from the development of the industrial sector for five consecutive years as well as data on the number of workers who work during the year 2009-2013. This research includes the type of descriptive quantitative research using linear regression analysis techniques. The results of this study showed, a significant influence between the number of industries on the absorption of the amount of labor. Thus the number of industries there is a positive and significant influence between the number of industries partially to the absorption of the number of labor in Surabaya. With this result the industrial sector in Surabaya City is still in great demand by the people of Surabaya City to be the main choice in choosing a job, certainly if the number of industries has an influence on the absorption of labor, then the industrial sector including one powerful way to reduce the number of unemployed in Surabaya. If increasing the number of industries in the city of Surabaya is one way to reduce and overcome the number of unemployed should the government think of this as a way out such as facilitate permits and other policies that are more aligned to the industrial sector.Â Â Keywords: Industrial Sector, Labor, Unemployment